2019
DOI: 10.1111/pirs.12416
|View full text |Cite
|
Sign up to set email alerts
|

The monetary subjective health evaluation for commuting long distances in Chile: A latent class analysis

Abstract: Long‐distance commuting (LDC) is a growing phenomenon in specialized countries in extractive industries such as Chile. There has also been a growing concern about the potential impacts on the health of long‐distance commuters. This paper formalizes the relationship between commuting distance and self‐assessed health status and shows the monetary valuation of health costs for commuting long distances using a latent class approach. This econometric approach allows us to capture both preference and threshold hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…For example, Ross and Zenou () and Van Ommeren and Gutiérrez‐i‐Puigarnau () point out that commuting leads to increased absenteeism, and authors such as Koslowsky, Kluger, and Reich (), Evans, Wener, and Phillips () and Kahneman, Krueger, Schkade, Schwarz, and Stone (), among others, show the negative psychological effects that commuting can induce by raising worker stress levels. Similarly, Gottholmseder, Nowotny, Pruckner, and Theurl (), Hämmig, Gutzwiller and Bauer (), Hansson, Mattisson, Björk, Östergren, and Jakobsson (), Roberts, Hodgson and Dolan (), Sandow, Westerlund and Lindgren () and Palomino and Sarrias (), explore other harmful effects of commuting on health, in dimensions such as obesity, insomnia and increased likelihood of accidents and mortality, among others. Many of these studies point to the existence of variables that moderate these effects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Ross and Zenou () and Van Ommeren and Gutiérrez‐i‐Puigarnau () point out that commuting leads to increased absenteeism, and authors such as Koslowsky, Kluger, and Reich (), Evans, Wener, and Phillips () and Kahneman, Krueger, Schkade, Schwarz, and Stone (), among others, show the negative psychological effects that commuting can induce by raising worker stress levels. Similarly, Gottholmseder, Nowotny, Pruckner, and Theurl (), Hämmig, Gutzwiller and Bauer (), Hansson, Mattisson, Björk, Östergren, and Jakobsson (), Roberts, Hodgson and Dolan (), Sandow, Westerlund and Lindgren () and Palomino and Sarrias (), explore other harmful effects of commuting on health, in dimensions such as obesity, insomnia and increased likelihood of accidents and mortality, among others. Many of these studies point to the existence of variables that moderate these effects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…That individuals in class 2 actually enjoy their commute trip from home to work, together with the fact that this class prefers more populated cities, may be explained by the fact that young men, with little education, low socioeconomic status and living in less populated cities (outside the metropolitan region of Santiago) are more likely to belong to this class. It has been shown that individuals with such characteristics are more likely to derive utility for activities that can be conducted while travelling (because they enjoy driving or engage in more active commuting) or may derive enjoyment from the commuting itself (Mokhtarian & Salomon, 2001; Páez & Whalen, 2010; Palomino & Sarrias, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…LSA allows researchers to value in monetary terms a change in a certain amenity on individuals' subjective well‐being (or some proxy to individuals' utility) using a compensating variation approach (Clark & Oswald, 2002). LSA has been used to assess the monetary valuation of climate and weather conditions (Ferreira & Moro, 2010; Frijters & Van Praag, 1998; Maddison & Rehdanz, 2011), crime (Brenig & Proeger, 2018; Moore, 2006; Moore & Shepherd, 2006), pollution or environmental (Luger, 1996; Luechinger, 2009; 2010; Levinson, 2012), commuting (Palomino & Sarrias, 2019), green areas (Ambrey & Fleming, 2014), and more general amenities (Ahumada, Iturra, & Sarrias, 2019; Sarrias, 2019).…”
Section: Introductionmentioning
confidence: 99%